2018
DOI: 10.1016/j.solmat.2018.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Anti-soiling coatings for solar cell cover glass: Climate and surface properties influence

Abstract: The objective of this study has been twofold: i) to investigate different strategies for CPV module glass surface modification, in particular preparing hydrophilic and hydrophobic coatings in order to reduce the dust accumulation (soiling) on the module surface; ii) to perform a joint comparative soiling testing in Italy, Spain and Brazil in order to understand the limit and advantages of the proposed anti-soiling coatings in different climate condition. Two TiO 2 /SiO 2 films with different titanium content h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 26 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…Coatings 2019, 9, x FOR PEER REVIEW 2 of 10 of application [8]. Solar energy applications are also taking advantage of the efficiency increase over time, due to the soiling reduction in the optical surfaces through this kind of coatings [9], mainly in photovoltaic technology [10][11][12] but also more recently in CSP plants [13][14][15]. For CSP applications, anti-soiling coatings are applied both to the glass tubes of parabolic-trough collectors and to solar reflectors of all different concentrators.…”
Section: Methodsmentioning
confidence: 99%
“…Coatings 2019, 9, x FOR PEER REVIEW 2 of 10 of application [8]. Solar energy applications are also taking advantage of the efficiency increase over time, due to the soiling reduction in the optical surfaces through this kind of coatings [9], mainly in photovoltaic technology [10][11][12] but also more recently in CSP plants [13][14][15]. For CSP applications, anti-soiling coatings are applied both to the glass tubes of parabolic-trough collectors and to solar reflectors of all different concentrators.…”
Section: Methodsmentioning
confidence: 99%
“…In another studies of de Jesus, SiO 2 sol-gel treated with hexamethyldisilazane (referred to as SM) resulted in a hydrophobic thin film [ 35 ]. In comparison with their previous TiO 2 /SiO 2 composite, it had much higher transparency, which is even superior to the bare glass ( Figure 8 ).…”
Section: Hydrophobic Coatingsmentioning
confidence: 99%
“… Transmittance spectrum for uncoated glass plate and glass with the layer of hydrophobic film (SM), hydrophilic Si 86 Ti 14 (ST1), hydrophilic Si 40 Ti 60 (ST2), and pure TiO 2 (T) [ 35 ]. …”
Section: Figurementioning
confidence: 99%
“…However, most contributions have studied the self-cleaning properties in laboratory conditions, [13][14][15][16] while only few ones have investigated the performances of self-cleaning coatings by testing them in atmospheric outdoor conditions. Magnum et al [17] have reported the preparation of anti-soiling coatings composed by superhydrophilic/hydrophobic thin films tested in different locations (Brazil, Italy, and Spain) in out-door conditions. The best performances were obtained with TiO 2 -SiO 2 composite film, which showed a persistent superhydrophilic character with water contact angles near to 0°and transmittance losses of 50 %.…”
Section: Introductionmentioning
confidence: 99%